Penerapan Metoda Six Sigma DMAIC untuk Mengurangi Cacat Pakaian 514 (Studi Kasus di CV Jaya Reksa Manggala) - Sugih Sudharma Tjandra; Nixon Setia Utama; Hanky Fransiscus (Jurnal Rekayasa Sistem Industri, 2018)
CV Jaya Reksa Manggala (JRM) is one of clothing company. With increasing competition in this clothing company, the companies are required to keep improving the quality of clothing products. One of the important things in quality is reduction of product defects. One of the proven methods of  quality improvement is the Six Sigma DMAIC method, which is a continous improvement method that aims to achieve the best quality. One of the products of CV JRM which is still have a lot of defects is 514 products. From the initial data obtained, DPMO value for process I and II for 514 products is 10,768.52 and 27,341.42 with sigma level 3.79 and 3.43. The steps undertaken in this Six Sigma DMAIC method include define, measure, analyze, implementation and control. Several proposed improvements were then made to reduce the problem of these defects and from the data at the control stage, the DPMO values of processes I and II became 2,941.76 and 1,812.69 with sigma levels of 4.25 and 4.41. From this result it can be said that with Six Sigma DMAIC method, there is improvement of quality for product 514 at CV JRM.